Feasiblity of anthropometric measurements for large-scale application in the Irish longitudinal study on ageing in people with intellectual disability (IDS-TILDA) : an exploratory study - Swinburne, Janet (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2014)
Malnutrition, either as under- or over-nutrition, is a risk factor for increased morbidity and mortality, and overweight and obesity represent one of the most pressing public health concerns of our time. Effective identification, prevention, treatment and monitoring of malnutrition require effective and high-quality assessment to guide interventions and measure their success. Yet no nationally representative anthropometric data on adults with intellectual disability (ID) exists in Ireland.
Keywords: Nursing and Midwifery, Ph.D.; Ph.D. Trinity College Dublin